Toy library and recreational activities: A care tool in child hospitalization (Research, Society and Development, 2022)
This was a bibliographical narrative research that had as its object the benefits perceived by the nursing staff in hospitalized children with the use of the toy library. Objective: To verify the perception of child nursing professionals in pediatrics in hospitals that use the toy library. List the recreational activities developed in pediatrics with hospitalized children. Raise the benefits perceived in the child from the use of the toy library or the development of playful activities with those who cannot leave the bed. The collected material was analyzed and the data grouped according to the points of convergence. The lack of scientific articles on the searched topic was evidenced. During the study, the importance of using the toy library as a therapeutic strategy that facilitates the recovery of hospitalized children and the difficulties encountered by nursing professionals in using the toy library as adjunct therapy to the treatment of the disease was perceived.